Method for optimizing availability of optical telecommunication network in presence of correlated failures: doctoral thesis - Miletić, Vedran (V. Miletić ; Fakultet elektrotehnike i računarstva, 2015)
The work describes the design goals and methodology in creating a new model of optical telecommunication network used for studying network resilience. The model is implemented by discrete-event network simulator ns-3. The advantages of using the existing simulator core infrastructure provided by ns-3 are analyzed and compared to building own simulator from scratch, or selecting a tool among other existing simulators such as ns-2, OMNeT++, and commercial simulators. The requirements for feature functionality are outlined and high-level overview of the model architecture and its components are provided. The model is extended to support availability evaluation.